OP0045 DELINEATION OF A PROINFLAMMATORY CYTOKINE PROFILE TARGETED BY JAK1/2 INHIBITION USING BARICITINIB IN A PHASE 2 SLE TRIAL. (2nd June 2020) - Dörner, T.; Tanaka, Y.; Petri, M. A.; Smolen, J. S.; Wallace, D.; Crowe, B.; Dow, E.; Higgs, R. E.; Rocha, G.; Benschop, R.; Silk, M.; De Bono, S.; et al.
Abstract : Background: Given the unmet clinical needs in systemic lupus erythematosus (SLE), including poor disease control and drug toxicities, new therapies are needed. In a phase 2, randomized, placebo-controlled, double-blind study (JAHH), once-daily baricitinib (bari) resulted in significant clinical improvement in patients (pts) with active SLE versus PBO. Bari inhibits JAK1 and JAK2 signalling, and in turn may affect STAT1, STAT2, STAT4 pathways. Therefore, bari has the potential to simultaneously impact several pro-inflammatory immune cytokines implicated in the pathogenesis of SLE, including IFN-α, IFN-γ, IL-6, IL-12, and IL-23. Objectives: The objectives of the current study were: 1) to examine baseline serum cytokines in the JAHH phase 2 clinical trial for correlations with clinical or immunologic assessments; 2) to determine if changes in serum cytokine levels were associated with bari treatment. Methods: Pts enrolled in the JAHH phase 2 trial received daily treatment with PBO, bari 2 mg, or bari 4 mg through week 24. Serum samples were collected at baseline (week [wk] 0), wk 12, and wk 24) from SLE pts (n=270) and 50 sex- and age-matched controls. Samples were analyzed for: IL-2, IL-3, IL-5, IL-6, IL-10, IL-17A, IL-21, IL-12/23p40, IL-12p70, GM-CSF, IFN-α and IFN-γ using ultrasensitive quantitative assays. IFN gene signature, autoantibodies, C3 and C4 were measured as previously described [1]. Results: At wk 0, serum IL-17A, IL-12/23p40, IL-6, IFN-γ and IFN-α were readily detectable. IL-12/23p40 was detectable in 100% of pts vs. 100% of controls, IFN-γ in 89% of pts vs. 66% of controls, IL-6 in 53% of pts vs. 12% of controls and in IFN-α 41% of pts vs. 2% of controls; detection of serum IL-2, GM-CSF, IL-5, IL-10 and IL-17A was variable (Fig 1 ). At baseline (wk 0), IL-12/23p40 was positively correlated with SLEDAI and IFN gene signature and negatively correlated with serum C4. IL-6 was positively correlated with joint swelling, joint tenderness, IFN-γ and C3. Serum IFN-α was positively correlated with serum IFN-γ, anti-Sm and anti-RNP, and the IFN gene signature (Fig 2 ). Treatment with bari 4 mg (Fig 1B ) significantly decreased serum IL12/23p40 and IL-6 cytokine levels at wk 12 (p<0.05) but not serum IFN-α or IFN-γ levels (Fig 1B ). Conclusion: Bari 4 mg treatment was associated with statistically significant decreases of serum IL-12/23p40 and IL-6 at week 12 which continued through week 24. Serum IFN-α or IFN-γ were not reduced with bari treatment. Thus, bari 4 mg simultaneously impacted multiple pro-inflammatory cytokines implicated in the pathogenesis of SLE. References: [1]Hoffman RW, et al. Arthritis Rheumatol. 2017;69(3):643-654. Disclosure of Interests: Thomas Dörner Grant/research support from: Janssen, Novartis, Roche, UCB, Consultant of: Abbvie, Celgene, Eli Lilly, Roche, Janssen, EMD, Speakers bureau: Eli Lilly, Roche, Samsung, Janssen, Yoshiya Tanaka Grant/research support from: Asahi-kasei, Astellas, Mitsubishi-Tanabe, Chugai, Takeda, Sanofi, Bristol-Myers, UCB, Daiichi-Sankyo, Eisai, Pfizer, and Ono, Consultant of: Abbvie, Astellas, Bristol-Myers Squibb, Eli Lilly, Pfizer, Speakers bureau: Daiichi-Sankyo, Astellas, Chugai, Eli Lilly, Pfizer, AbbVie, YL Biologics, Bristol-Myers, Takeda, Mitsubishi-Tanabe, Novartis, Eisai, Janssen, Sanofi, UCB, and Teijin, Michelle A Petri Grant/research support from: GSK, Eli Lilly and Company, Consultant of: Eli Lilly and Company, Josef S. Smolen Grant/research support from: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Consultant of: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Daniel Wallace Consultant of: Amgen, Eli Lilly and Company, EMD Merck Serono, and Pfizer, Brenda Crowe Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Ernst Dow Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Richard E Higgs Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Guilherme Rocha Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Robert Benschop Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Maria Silk Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Stephanie de Bono Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Robert Hoffman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Damiano Fantini Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company